Behavior Analysis of Controllable Electrorheology Fluid Plain Journal Bearings - Lee, Yong-Bok (ASME, 2015)
Electrorheological (ER) lubricant is applied to a rigid rotor system supported by a hydrodynamic bearing that is subjected to a sudden imbalance and a dynamic periodic rotating load. The pressure of the ER film, which exhibits a Bingham flow, varies with the electrical field strength and depends on the yield shear stress and the thickness of the ER fluid film. The ER lubricant was found to offer a good load capacity relative to a Newtonian lubricant and its performance could be controlled to handle sudden dynamic loads. Increasing the magnitude of the electric field strength provides a greater load capacity within certain physical limitations and also reduces the magnitude of an unbalanced force due to unbalanced mass and vibration caused by vibration in the dynamically rotating load. These results could be applied to the control of a suddenly imbalanced system, such as one with rotor blades, or for reducing vibration in cyclic loading rotor systems, such as in internal combustion engines.